2011
DOI: 10.1111/j.1600-0501.2010.02116.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the accessory mental foramen using rotational panoramic radiography compared with cone‐beam computed tomography

Abstract: Approximately half of the accessory mental foramina-positive CBCT images demonstrated the accessory mental foramen, or bony canal between the point of bifurcation from the mandibular canal and accessory mental foramen on rotational panoramic radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 14 publications
6
52
3
8
Order By: Relevance
“…Any NFs observed were excluded from this study. The reported frequency of occurrence ranges from 5.7% to 8.3% in previous CBCT studies (5,(8)(9)(10)(11). In the present study, the rate of AMF presence was 6.3%, similar to rates found in previous studies (Table 5).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Any NFs observed were excluded from this study. The reported frequency of occurrence ranges from 5.7% to 8.3% in previous CBCT studies (5,(8)(9)(10)(11). In the present study, the rate of AMF presence was 6.3%, similar to rates found in previous studies (Table 5).…”
Section: Discussionsupporting
confidence: 80%
“…Multiple MFs have only been reported and evaluated using CBCT images in some studies (5,(8)(9)(10)(11)(12). The foramina located in the surrounding region of the MF have been reported as AMFs although there is no clear definition for AMFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,11 In accordance with previous studies, the mean long axis was found to be 1.4 mm (SD ¡0.4 mm) in this study. The mean area of the ABFs was found to be 1.7 mm 2 and 1.5 mm 2 in different studies performed by Naitoh et al 5,18 Similar to those studies, we found a mean diameter of 1.5 mm 2 (SD ¡0.8 mm 2 ). Also, Naitoh et al 5 reported that the distance between the mental foramen and the ABF ranged from 4.5 mm to 9.6 mm, with a mean of 6.3 mm.…”
Section: Discussionsupporting
confidence: 79%
“…[13][14][15][16][17] However, the frequency of ABFs was found to be 4%, 7.7% and 10.7% in CT-based studies performed in the last 3 years. 5,11,18 In the present study, 14 ABFs were detected in 10 of the 504 patients, and the frequency rate was found to be 2%, which is lower than that generally reported in the literature. There was no statistically significant difference in males and females and no significant gender differences were observed in the present and previous studies.…”
Section: Discussioncontrasting
confidence: 51%